Judicial Empirical Research on the Protection of Collective Assets and Shares of Migrant Workers in Cities - Zhang, Yan; Zhou, Hualin; Zhang, Jing (Journal of Theory and Practice of Engineering Science, 2023)
China's urbanization is a major event that affects the world's development process in the 21st century. The settlement of farmers in cities is of great significance for promoting new urbanization, alleviating the contradiction between people and land in China, fully leveraging the effectiveness of property rights, and improving China's rural economic system. The collective asset stock rights of farmers who settle in cities are legal rights protected by laws and policies, and can provide basic living security for farmers who settle in cities. However, the current protection of the collective asset and stock rights of farmers who have settled in cities is facing problems such as a lack of legal norms for collective asset and stock rights, unclear rules for the loss of membership qualifications, obstacles to the realization of shares, and incomplete judicial relief systems. It is necessary to focus on the drawbacks of the existing system, formulate relevant legal norms for the protection of collective asset and stock rights of farmers who have settled in cities, clarify the rules for the loss of membership, and improve the realization methods of collective asset and stock rights, Strengthen the construction of the judicial relief system for the collective assets and stock rights of farmers who have settled in cities, safeguard the legitimate rights and interests of farmers who have settled in cities, and promote the development of new urbanization.